Demographic and actuarial projections by means of Monte Carlo Markov chains - Morales Garay, Ismael (2017)
A description of the method of Monte Carlo Markov Chains is presented for actuarial demographic forecast, in regard to the mortality, disability, mortality of disabled lives among others. We include examples of how the method is implemented in the Pensions and Retirements Fund for Teachers in Costa Rica, as a input for the results of the actuarial valuation of the pension plan.